2012
DOI: 10.1111/j.1475-6811.2012.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Partner‐AMP and well‐being: Evidence for an implicit secure base script?

Abstract: The current research presents an adapted Affect Misattribution Procedure (AMP) to assess the aspects of the relational schema of romantic partners that are difficult to verbalize and tests the prediction that a positive implicit image of the partner constitutes a psychological resource that increases well-being. In Study 1, the partner-AMP predicted well-being in student participants even after controlling for explicit partner attitudes and socially desirable responding. In Study 2, the partner-AMP was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…To create idiographic stimuli for the indirect measure (AMP; Banse et al, 2010), participants received a form listing 11 categories of person attributes: first name, family name, hair color, eye color, profession, car, sport, hobby, favorite music, typical drink, and typical trait. To generate stimuli relating to their ex‐partner (ex‐partner primes), participants were asked to supply the first name and four additional relevant attributes for those categories that they most strongly associated with the ex‐partner.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To create idiographic stimuli for the indirect measure (AMP; Banse et al, 2010), participants received a form listing 11 categories of person attributes: first name, family name, hair color, eye color, profession, car, sport, hobby, favorite music, typical drink, and typical trait. To generate stimuli relating to their ex‐partner (ex‐partner primes), participants were asked to supply the first name and four additional relevant attributes for those categories that they most strongly associated with the ex‐partner.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has identified positive implicit and explicit attitudes toward the current partner to be related to greater life satisfaction (Banse & Kowalick, 2007; Banse et al, 2010). In contrast, implicitly hanging on to an ex‐partner may contribute to misery, as continued attachment to an ex‐partner is problematic for postbreakup adjustment (Frazier & Cook, 1993).…”
Section: (Ex‐)partner Attitudes and Well‐beingmentioning
confidence: 99%
See 3 more Smart Citations